2018
DOI: 10.1097/j.pain.0000000000001409
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of gendered and ungendered pain relief norms and stereotypes using Q-methodology

Abstract: Pain is ubiquitous, but effective pain relief eludes many. Research has shown that some pain behaviours are perceived as gendered, and this may influence the way men and women express and cope with pain, but such enquiries have not extended to specific methods of pain relief. Our aim was to explore perceptions of the most socially acceptable ways for men and women to relieve pain. Across two studies, sixty participants (50% male) aged 18-78 completed a Q-sort task, sorting different pain relief strategies by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…A similar effect was not found for crying, however, although we did find women viewed holding the body as more indicative of a how women express pain. These findings are consistent with work into gender‐based expectations around pain coping (Keogh & Denford, ; Wratten et al, ). They also relate to evidence that gender‐based expectations affect how health care providers judge the pain of others (Bernardes, Costa, & Carvalho, ; Hirsh, Hollingshead, Matthias, Bair, & Kroenke, ; Samulowitz, Gremyr, Eriksson, & Hensing, ; Schafer, Prkachin, Kaseweter, & Williams, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A similar effect was not found for crying, however, although we did find women viewed holding the body as more indicative of a how women express pain. These findings are consistent with work into gender‐based expectations around pain coping (Keogh & Denford, ; Wratten et al, ). They also relate to evidence that gender‐based expectations affect how health care providers judge the pain of others (Bernardes, Costa, & Carvalho, ; Hirsh, Hollingshead, Matthias, Bair, & Kroenke, ; Samulowitz, Gremyr, Eriksson, & Hensing, ; Schafer, Prkachin, Kaseweter, & Williams, ).…”
Section: Discussionsupporting
confidence: 86%
“…Experimental studies confirm that identification with masculine traits are associated with higher pain thresholds, whereas identification with feminine traits are related to greater pain sensitivity (Alabas, Tashani, Tabasam, & Johnson, ). Gender also affects how pain is expressed and responded to (Bernardes & Lima, ; Bernardes, Silva, Carvalho, Costa, & Pereira, ; Robinson et al, ; Wratten, Eccleston, & Keogh, ).…”
Section: Introductionmentioning
confidence: 99%
“…If sex and gender affect the way observers respond to those in pain, the question is whether this is due to gender-based beliefs and expectations. Empirical studies confirm the existence of stereotypical gender beliefs about pain (Bernardes, Silva, Carvalho, Costa, & Pereira, 2014;Keogh & Boerner, 2020;Keogh & Denford, 2009;Robinson, Gagnon, Dannecker, et al, 2003;Wesolowicz, Clark, Boissoneault, & Robinson, 2018;Wratten, Eccleston, & Keogh, 2019). For example, found that women are viewed as more sensitive to pain, and men less willing to report pain to others.…”
Section: Do Observers View Men and Women's Pain In A Similar Way?mentioning
confidence: 91%
“…Keogh and Denford (2009) found expectations that women catastrophise more than men, and that men use distraction more than women. Wratten et al (2019) found that some pain coping strategies are considered more masculine (e.g., swearing, alcohol use), whereas other strategies are viewed as more feminine (e.g., crying, social support). Some studies also find that such stereotypical gender-based beliefs affect how individuals judge the pain of others (Hobara, 2005;Robinson & Wise, 2003;Schafer et al, 2016).…”
Section: Do Observers View Men and Women's Pain In A Similar Way?mentioning
confidence: 99%
“…2,45,63 Stereotypical gender beliefs and expectations about pain are also relevant. 21,96,99,197 For example, men are considered less expressive and more likely to engage in avoidance when in pain, whereas women are perceived to be more likely to catastrophize and cry. Importantly, these beliefs have been shown to impact on how pain is expressed and responded to, [156][157][158] including with pain medication use.…”
Section: Individual Gender Context Of Painmentioning
confidence: 99%